Democratic Republic of Sao Tome and Principe : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Second National Poverty Reduction Strategy II (NPRS-II) (2012-2016) for Democratic Republic of Sao Tome and Principe. A comparison of the results of the 2000 and 2010 poverty profile, based on the average income method, shows that there was progress in reducing poverty, albeit far less than expected. The ratio of the incidence of poverty decreased from 53.8 percent in 2000 to 49.6 percent in 2010, representing a reduction of 4.2 percentage points, which is far below the target set in the NPRS-I for 2010, and also shows relative improvement in the depth of poverty.